منهج مدرسة المنار في التّفسير بالرّأي: Al-Manar School’s Approach to Interpretation by Opinion - Alkhattb, AQ. Waddah; Saged, Ali Ali Gobaili; Mohd Yusoff , Mohd Yakub @ Zulkifli (Jurnal Usuluddin, 2023)
This study dealt with the situation of Sheikh Muhammad Abduh School, may God Almighty have mercy on him, which became famous as the al-Manar School of interpretation of the Holy Qur’an with opinion. And if al-Manar School was known for its intellectual orientation, it is assumed that it would move powerfully towards interpretation by opinion based on linguistic sciences. Humanity and nature, but the research shows that this use was within the limits of the curriculum Al-Hidai in interpretation, which focuses more on purposes and objectives than on means and tools, they used these sciences in interpretation as means to understand the purposes and did not tend to digress in them, and on the other hand, despite the clarity of the theoretical approach of the school, and the practical follow-up to it, the researchers did not exclude violations of it in several placements, the most influential in most of them were following the rational approach, and submitting it to Text. It is worthy of this experiment to follow its example, with its positive aspects, while avoiding the intakes contained in the research.